2012
DOI: 10.1002/joe.21422
|View full text |Cite
|
Sign up to set email alerts
|

“Statistical correctness”: Do demographic‐based strategies bring about corporate diversity?

Abstract: Questioning the usefulness of naïve conceptions of gender and diversity that run in much of the managerial literature, the authors used a series of qualitative interviews with women in top managerial positions in large French corporations to examine corporate gender diversity discourses and strategies. They found that recruiting women in top management positions does not systematically produce the sort of diversity targeted by corporate strategies. Moreover, evidence shows that the corporate diversity strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this sense, looking at policies is important. Bigo and Martin () have further noted that to effectively look at how gender diversity truly impacts firm performance, we must take into account corporate diversity policies. It is their existence and implementation that truly changes the culture of an organization and impacts social performance.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…In this sense, looking at policies is important. Bigo and Martin () have further noted that to effectively look at how gender diversity truly impacts firm performance, we must take into account corporate diversity policies. It is their existence and implementation that truly changes the culture of an organization and impacts social performance.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…On the other hand, the previous inconclusive results also foster the need to rethink the role of BGD in GI theoretically. In this regard, the national level and international level (Yasser et al, 2017) institutional and resource base contexts have been found significant for their impacts in the inconclusive relationship between BGD and different variants of sustainability (Bigo & Martin, 2012; Dong et al, 2022; Landry et al, 2016) however, those studies only considers vital macro‐economic and macro‐institutional indicators (García‐Sánchez et al, 2020). Within a country's institutional settings, the variation of the BGD‐GI relationship has been overlooked at par (Galbreath, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that the tradeoff between the stakeholders' pressures is dependent upon the insistence and salience of different stakeholders, and BGD only leverages its contribution in prioritization of the goals as per the resource base of their feminine capabilities (Fatima & Elbanna, 2023; Yang et al, 2018), BGD turns out to be a double‐edged sword (Triana et al, 2014). The role of women in addressing stakeholders' demands and their impact on sustainability constructs varies depending on the country, industry, and firm level contexts (Bigo & Martin, 2012). However, the role of women in archetypical field of subnational regions has not been explored yet (Galbreath, 2019; Naveed et al, 2021).…”
Section: Context Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%